IRMOF-8: theoretical evaluation of aluminum doping on hydrogen, methane, and hydrogen sulfide adsorption - Rodrigues, Nailton Martins (2020)
The use of porous materials, aimed at increasing gas storage capacity at lower pressures, exploits physical adsorption and is an emerging strategy that is being widely investigated. In this scope, porous materials such as metal organic frameworks (MOFs) are a viable alternative, where structural modifications can enhance the properties of these materials and improve the degree of adsorption for a given gas. In this work, we evaluated the adsorption of methane, hydrogen, and hydrogen sulfide gases on pure isoreticular MOF (IRMOF)-8 and aluminum-doped IRMOF-8 using density functional theory Perdew-Burke-Ernzerhof/DZVP and semiempirical AM1, PM3, PM6, PM6-DH+, PM6-DH2, PM6-D3, and PM7 methods. Adsorption isotherms were calculated by means of Grand Canonical Monte Carlo simulations. It was found that doping did not provide a significant increase in the amount of adsorbed methane and hydrogen gases. Conversely, doping led to a considerable increase for hydrogen sulfide capture